Measuring the public’s willingness to pay for the rejuvenation of Raffles Place Park in Singapore : a contingent valuation approach - Lim, Bryan (Nanyang Technological University, 2020)
With the recent announcement of the Master Plan 2019, there has been a pique in interest regarding the development of the public spaces in Singapore. Raffles Place Park has been briefly mentioned in the Master Plan 2019 but upon further examination, we found no concrete plans for the rejuvenation and development of the park. Given this backdrop and to fill the gap in the literature, this paper aims to elicit Singaporeans’ willingness to pay for three unique design concepts: namely, Greenery, Events and Arts and Culture. These concepts were carefully constructed based on relevant literature and successful case studies. Using the widely adopted Contingent Valuation Method (CVM) and a sample size of 400, this empirical study estimated Singapore residents’ willingness-to-pay for each of the design concepts. Subsequently, this paper identified Greenery as the most valued design concept at $8.26 followed by Arts and Culture at $4.07 and lastly Events at $3.56. In addition, determinants for WTP were identified for each design concept. The results of this study would be meaningful in assisting the URA and relevant authorities in maximizing social benefits for the costs spent in rejuvenating Raffles Place Park.